2020
DOI: 10.1080/14739879.2019.1710863
|View full text |Cite
|
Sign up to set email alerts
|

Educational expectations of professionals who teach in primary health care in Chile

Abstract: With more emphasis on primary health care (PHC) both in the undergraduate and postgraduate curriculum, there is an increasing demand for high quality teaching in primary care centres. However, professionals in low and middle income countries often have little training in teaching. Britain could have an important role in supporting training the trainers in other countries. However the needs of these PHC teachers may differ from those teaching in British PHC. We explore the needs of professionals who teach in PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…We used a mixed method approach to collect the data; first an online survey was conducted on the needs of doctors who work and teach in PHC in Peru (see Supplementary File 1). The survey was created based on the domains of teaching competence defined by Sherbino, Frank and Snell (2014) and was validated with a panel of PHC expert physicians ( Moore et al , 2020 ). The survey included questions on sociodemographic variables, the importance of 10 competencies for teaching, and the form and feasibility of conducting training in teaching skills for professionals working in PHC.…”
Section: Methodsmentioning
confidence: 99%
“…We used a mixed method approach to collect the data; first an online survey was conducted on the needs of doctors who work and teach in PHC in Peru (see Supplementary File 1). The survey was created based on the domains of teaching competence defined by Sherbino, Frank and Snell (2014) and was validated with a panel of PHC expert physicians ( Moore et al , 2020 ). The survey included questions on sociodemographic variables, the importance of 10 competencies for teaching, and the form and feasibility of conducting training in teaching skills for professionals working in PHC.…”
Section: Methodsmentioning
confidence: 99%
“…Instructing medical students was perceived as a skill to be continuously developed, though some studies reported a lack of confidence in teaching abilities. 29,41 While some articles investigated residents' clinical teaching experiences, many described practicing physicians who started teaching only when they became attending physicians. 31,40 Without prior experience or formal teacher training, many reported acquiring the skills by learning experientially.…”
Section: Perceptions Of Clinical Teachingmentioning
confidence: 99%
“…Clinician teachers' educational approaches and teaching strategies were diverse. 23,39,41 Informal or ad hoc teaching was frequently used to address student-directed learning objectives. Some taught with an observation-and-feedback approach, in which students were given autonomy and subsequently were evaluated on their performance.…”
Section: Clinical Teaching Strategiesmentioning
confidence: 99%
See 2 more Smart Citations